As relações entre arranjo institucional e representação política nos conselhos - Joana Vaz Moura (Ciências Sociais Unisinos)
The creation of institutional spaces for social participation has originated a new form of political representation. Representatives who act in these spaces speak on behalf of a particular social group that needs a spokesperson to present its interests. The normative theory of representation tends to take the existence of an interest to be represented as something given, and that it would fit to the representative to assume these interests and to express them in the Councils. However, as some authors of the relational approach emphasize, the act of representation is a moment of symbolic construction of those on behalf of whom the representative intends to speak. This article focuses on the relationship between the actions of social actors and the political-institutional configuration in the Councils. It seeks to deepen this analysis from a relational approach, which may allow further analytic treatment of some factors (institutional arrangements, profile and trajectory of the council members).